Desire for Success Awakens: Proof of Competence Restoration in a Non-competitive Environment - Meng, Liang; Pei, Guanxiong; Zhang, Yupei; Jin, Jia (Frontiers in Neuroscience, 2021)
Pioneering studies reported that individuals who worked on a highly difficult task and experienced competence frustration beforehand would activate a restorative process and show enhanced autonomous motivation in a subsequent irrelevant activity. In this follow-up study, we explored the effect of prior competition outcome on one’s autonomous motivation in a subsequent non-competitive environment. According to our experimental manipulation, participants were randomly assigned to two treatment groups (a winning group and a losing group) and a control group. The experiment lasted for three sessions. Participants in the control group completed a single-player stop-watch (SW) task all along, while those in both treatment groups worked on a competitive SW task and competed for monetary rewards during Session 2 only. Electrophysiological data in Session 1 serve as the baseline and measure one’s trait-level autonomous motivation towards the SW game. For participants in the losing group, more pronounced difference wave of feedback-related negativity was observed in Session 3 compared with Session 1, suggesting enhanced autonomous motivation in Session 3. Such a pattern was observed in neither the winning group nor the control group. These results suggested that failure in a prior competition would activate one’s competence restoration in a subsequent non-competitive environment. Task difficulty and social competition are varied sources of competence frustration. Thus, our findings advanced understanding of the competence restorative process and helped clarify the dynamics between competition and human motivation.